2015
DOI: 10.1210/jc.2014-2134
|View full text |Cite
|
Sign up to set email alerts
|

Human Uterine Leiomyoma Stem/Progenitor Cells Expressing CD34 and CD49b Initiate Tumors In Vivo

Abstract: CD34 and CD49b are cell surface markers that can be used to enrich a subpopulation of leiomyoma cells possessing stem/progenitor cell properties; this technique will accelerate efforts to develop new therapies for uterine leiomyoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 20 publications
6
76
0
3
Order By: Relevance
“…Interestingly, CD34+/CD49b- cells had intermediate levels of these stem cell factors compared to CD34-/CD49b- cells. Additionally, ER-alpha and PR were significantly underexpressed in CD34+/CD49b+ cells, consistent with prior studies on SP, and CD34+/CD49b- cells again showed intermediate expression levels between CD34+/CD49b+ and CD34-/CD49b- cells[78**]. Taken together, these results led us to hypothesize that CD34+/CD49b+ cells are largely fibroid somatic stem cells, capable of asymmetric division allowing both self-renewal and the production of intermediary daughter cells, or CD34+/CD49b-cells, which ultimately develop into fully differentiated fibroid cells, or CD34-/CD49b- cells.…”
Section: Somatic Stem Cellssupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, CD34+/CD49b- cells had intermediate levels of these stem cell factors compared to CD34-/CD49b- cells. Additionally, ER-alpha and PR were significantly underexpressed in CD34+/CD49b+ cells, consistent with prior studies on SP, and CD34+/CD49b- cells again showed intermediate expression levels between CD34+/CD49b+ and CD34-/CD49b- cells[78**]. Taken together, these results led us to hypothesize that CD34+/CD49b+ cells are largely fibroid somatic stem cells, capable of asymmetric division allowing both self-renewal and the production of intermediary daughter cells, or CD34+/CD49b-cells, which ultimately develop into fully differentiated fibroid cells, or CD34-/CD49b- cells.…”
Section: Somatic Stem Cellssupporting
confidence: 89%
“…Originally, fibroid stem cells were isolated using the Hoechst dye exclusion technique for side populations (SP)[75, 76], however, the SP technique is expensive, exhibits significant sensitivity to minor staining variations, and is detrimental to cell survival, making further study of fibroid cells difficult[77]. As a solution to these pitfalls, we recently reported a novel way of isolating fibroid stem cells using cell surface markers CD34 and CD49b[78**]. Cell sorting using antibodies to these cell surface proteins revealed 3 distinct cell populations: CD34+/CD49b+, CD34+/CD49b-, and CD34-/CD49b- cells (figure 2).…”
Section: Somatic Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that human uterine leiomyoma stem/progenitor cells expressed CD34 and CD49b, which initiate tumors in vivo …”
Section: Introductionmentioning
confidence: 99%
“…5 Recently, it was shown that human uterine leiomyoma stem/progenitor cells expressed CD34 and CD49b, which initiate tumors in vivo. 6 Pathological alterations of signaling pathways have been recognized as a key feature in a variety of human diseases. 7 The successful development of protein tyrosine kinase inhibitors (PTK) has suggested them as candidates for 'signal transduction therapy'.…”
Section: Introductionmentioning
confidence: 99%